The Cosmopolitan Consideration of Human Rights in the 21st Century - Garrido Gómez, María Isabel (Ius Humani. Jornal do direito, 2025)
This paper begins by clarifying the diverse terminology of human rights and their different meanings, which have emotionally charged effects, with a plurality of opinions and moral codes. Furthermore, it is noted that rights constitute the substantive version of democracy, with a problem of the functioning of democracies, without forgetting the question of the possibilities of technical and political implementation. It analyses the connection with human dignity, an ethical minimum that must be observed and serves as a basis for affirming the universality of human rights, and the relationship between human rights and public ethics, focusing on the moral, legal, and social spheres. From this perspective, it aims to study the universality of human rights at the present time, presenting real problems in their operationalization. The final reflection leads us to affirm that cosmopolitanism must gradually take the place of national citizenship, signifying the connection of universality with diversity.